Juegos verbales y el lenguaje oral en niños de preparatoria de la Escuela de Educación Básica Municipal “Capulí Loma”, ciudad de Loja, periodo 2023-2024 - Vega Condoy, Ariana Mishelle (2024)
Oral communication is a form of communication carried out through the use of spoken language. It is a complex system that involves the production and perception of sounds, the grammatical structuring of phrases and sentences, and the comprehension of both literal and contextual meaning. Oral language is essential for social interaction, learning, knowledge transfer, expression of emotions, and coordination of activities in daily life. It is a skill that people naturally develop at an early age and can also be studied in fields such as linguistics, psychology, and education. The research was conducted to determine the influence of verbal games on the development of oral language in preschool children at "Capulí Loma" Municipal Basic Education School in Loja City. A mixed approach was implemented to combine quantitative and qualitative data, along with a quasi-experimental design. Inductive-deductive methods were used to facilitate the analysis of the presented problem, and the Navarra-Revised Oral Language Test (PLON-R) was employed, administered to a sample of eighteen children. In the pre-test, 78% were found to be delayed, 11% needed improvement, and 11% were normal, showing difficulties in various pronunciations of words, identifying objects, and describing phrases. Subsequently, at the end of the activity guide, a post-test was conducted, resulting in 28% delayed, 5% needing improvement, and finally, 67% showing an increase in normalcy. It is concluded that the use of verbal games as a methodological tactic significantly influences children's acquisition of new knowledge in their language development. Keywords: Grammatical structuring, interaction, verbal games, spoken language, perception of sounds.